STUDYING THE EFFECTIVENESS OF USING ROBOTIC SIMULATORS, VIRTUAL REALITY, AND OTHER INNOVATIVE TECHNOLOGIES IN RESTORING HIP JOINT FUNCTIONS - Аншикин, Денис; Чорний, Владислав (SWorldJournal, 2025)
Today, a variety of innovative technologies, including robotic simulators and virtual reality tools, can be used for comprehensive rehabilitation of lower limb injuries. Such new approaches to rehabilitation can speed up the recovery process and make it m